(untitled) (Global Journal of Medical Research, 2022)
Introduction: Pseudocyst of pinna is not very common problem in ENT practice. This is a benign painless cystic swelling arising in pinna and visible on lateral surface of pinna. No obvious cause of this swelling can be identified. This is an intra cartilaginous cyst without any epithelial lining. So, the name pseudocyst. There is no definite and effective medical treatment for this pseudocyst. There are so many surgical treatments available. We describe a novel minimal surgical technique for this condition. Methods: 24 patients 19 male and 5 female ages ranging from 25 -45 years were included in this trial. All patients were selected from ENT out patient department of Khulna Medical College Hospital and from my private consultancy Clinic between 1st January 2015 to 31st December 2018.